KARAKTERISTIK BUDAYA ORGANISASI UNGGUL SEBAGAI UPAYA MENINGKATKAN KINERJA FREELANCERS PADA PT INDAH JAWARA UTAMA - Leonard Adrie Manafe; Jaka Nugraha (LP2M Universitas Bina Bangsa, 2021)
The fourth industrial revolution directs people to increasingly realize the importance of digitization. PT Indah Jawara Utama is a corporate in the digital business world which has many competitors. To ensure the suitability measurement, strategy, duty, and the resultant impact, the company must possess a good organizational behaviour. Organizational behaviour refers to a system which distinguishes an organization to others. It indicates that an organization upholds a set of characteristics of organizational behavior. This study aimed to identify the characteristic of strong organizational behaviors in PT Indah Jawara Utama as a company which engages in the production house, agency media, and event organizer. This study used a qualitative method with focused interview approach. The samples were determined by saturated sampling (census). Results obtained from this study states that six of seven characteristics of organizational behaviors are found in PT Indah Jawara Utama. Those are innovation and risk taking, attention to detail, outcome orientation, people orientation, team orientation, and stability.